Characterization and process optimization of Melastoma malabathricum l. extract - Ambarwati, Dessy (2011)
Melastoma malabathricum L.MML)or local name as senduduk, have demonstrated the presence of phenolic compound.The phenolic compound in plants has a role to inhibiting the growth of microorganism.Antimicrobial activity in plants has become an important area in the food and beverages industry; therefore natural preservatives will be very potential for more natural and fresh-like foods.In this study,to obtain the phenolic compound from MML was used extraction. Conventional extraction as heating,boiling,or refluxing can be used to extract phenolic,however,the disadvantages are the loss of phenolics due to ionisation, hydrolysis and oxidation during extraction as well as the long extraction time.In this thesis,the potentionals of ultrasonic technology in extraction was investigated.Comparation between ultrasonic-assisted extraction and classical extraction (homogenizer extraction)with incubated waterbath as a control were investigated to provide understandings of influence of ultrasonic irradiation on the production of phenolic compound in MML.Extracts were analyzed for phenolic compound (gallic acid,ellagic acid and total phenols compound).Folin Ciocalteau method was chosen for total phenols determination,while the phenolic acids (gallic acid and ellagic acid) were analyzed by using HPLC.Results showed that ultrasonic-assisted extraction was more effective to produce phenolic compound (gallic acid,ellagic acid and total phenol) from MML extract than using the classical extraction.Acid-hydrolysis method was found the best method for post-treatment process of MML extract to produce maximum phenolic compound. Some characterization studies also investigated to understandings about nutrient composition, chemical properties and antimicrobial activity of MML extract.MML extract showed inhibitory activity against microorganism,such as B.cereus,B.subtilis,S.typhi and E. coli.The extraction process of MML extract were studied in this thesis,namely solid-to-liquid ratio,extraction temperature and extraction time.Prior to conducting an experimental design approach,in this study was indentification the parameter range in extraction process. The experimental run and optimization were designed using Design Expert Software as suggested by Response Surface Methodology (RSM).The optimum extraction process for highest phenolic compound extracted were obtained at extraction temperature and extraction time of 59.96 °C and 92.55 min, respectively,whereas,the solid loading about 20.07 g. Under this condition,the yield of gallic acid,ellagic acid and total phenol was 1.79 mg/g, 0.16 mg/g and 15.10 mg GAE/g. The results obtained in this study have exposed capability of ultrasonic technology in extraction of phenolic compound. Further works are nevertheless required to provide deeper understanding the mechanisms involved to facilitate the development of an optimum system applicable to the industry.